The Influence Of Learning Management System Usability, Leadership Effectiveness And Information Transparency On Service Quality In Education: Penelitian - Yani, Indri; Hendratni, Tyahya Whisnu; Nudu, Josef Hernawan; Putrianti, Flora Grace; Sukmarani; Aswadi, Dana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The primary objective of this research is to measure the impact of a learning management system's (LMS) features, leadership effectiveness, and information openness on the quality of educational services. A quantitative explanatory approach with a sample of 200 students selected via purposive sampling was used for this research. The students who participated were those who had used an LMS for at least one semester and had interacted with the digital academic service system. Prior to conducting multiple linear regression analysis, the research tool was subject to a number of tests including validity, reliability, and classical assumptions. It was resulting that the three independent variables had a significant and positive impact on educational services. This research has made a theoretical contribution to the area of educational management in the digital age by identifying technology, leadership and transparency in information as essential in the process. The institutions can, as has been the case with research findings that have a practical nature, increase service quality by optimizing the LMS, reinforcing leadership, and providing clear and easily accessible information, as it is the case with research findings that have a practical nature.